2016
DOI: 10.1093/bioinformatics/btw271
|View full text |Cite
|
Sign up to set email alerts
|

CMsearch: simultaneous exploration of protein sequence space and structure space improves not only protein homology detection but also protein structure prediction

Abstract: Motivation: Protein homology detection, a fundamental problem in computational biology, is an indispensable step toward predicting protein structures and understanding protein functions. Despite the advances in recent decades on sequence alignment, threading and alignment-free methods, protein homology detection remains a challenging open problem. Recently, network methods that try to find transitive paths in the protein structure space demonstrate the importance of incorporating network information of the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…Extensive experiments demonstrate the power of our method on recovering missing associations, and on discovering associations for novel genes and/or diseases that are not seen in the training. Our framework is generic and can be readily applied to tackle other important problems in computational biology, such as drug disease association (Pushpakom et al, 2019) and homolog detection for protein structure prediction (Cui et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive experiments demonstrate the power of our method on recovering missing associations, and on discovering associations for novel genes and/or diseases that are not seen in the training. Our framework is generic and can be readily applied to tackle other important problems in computational biology, such as drug disease association (Pushpakom et al, 2019) and homolog detection for protein structure prediction (Cui et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We performed genome scans for small RNAs across 12 bee genomes (Table S2) using covariance models implemented with Infernal cmsearch using the gathering threshold for inclusion (--cut_ga) [45] to find all Rfam accessions in each bee genome. We used Spearman rank regressions to test for significant associations between miRNA copy-number and social biology.…”
Section: Methodsmentioning
confidence: 99%
“…We include a stringent filter against these putative structured RNAs being coding by requiring no significant hits to the nr database via BLASTx 12 and no significant p-values from RNAcode 13 , which narrowed our list of putative structured RNAs to 1,862. To avoid proposing the same structure multiple times, we filtered this list to 1,525 unique putative structured RNAs by ensuring the same structures do not match the same regions using CMsearch 15 . To ensure that the predicted structure motifs were transcribed, we calculated RPKM values specifically for the structure motifs (instead of the entire intergenic region), and found that 1,213 of these structures contained strong RNA-Seq signal (RPKM > 20).…”
Section: Rna-seq Along With Comparative Genomics Enables Targeted Himentioning
confidence: 99%
“…In separate searches after our Prokka 17 predictions were generated, we then searched for the Rfam 14 database against these predictions to determine overlap. CMsearch version 1.1.2 15,41 was used for all searches with an e-value cutoff of 1 x 10 5 considered as a significant match.…”
Section: Motif Searchesmentioning
confidence: 99%